Implementasi dan Pengujian Menggunakan Metode BlackBox Testing Pada Sistem Informasi Tracer Study - Zen, Muhammad; Irwan; Hafni; Ananda, M. Dea Putra (Bulletin of Computer Science Research, 2024)
The research is aimed at implementing and testing the information systems of the Tracer Study at Panca Development University using the BlackBox Testing method. The BlackBox test method is chosen to evaluate the functionality of the system without having to know the internal details of that system. Previous research results showed that BlackBox testing was effective in identifying functional errors without requiring in-depth knowledge of the internal structure of the system. In the context of information system development, the use of testing methods such as BlackBox Testing becomes essential to ensure that the developed system functions properly according to the needs of the user. Implementation of this method on the Tracer Study information system is expected to improve the quality of the system and ensure that the system can provide accurate and useful information to the user. Thus, the research contributes to the development of the information system Tracer Studies in the higher education environment, in particular Panca Budi Development University, with a testing approach that focuses on the external functionality of the systems. The results of the implementation and testing using the BlackBox Testing method are expected to improve the quality and reliability of the Tracer Study information system that can support better decision-making in the future.